Rekayasa Prototipe Piranti Lunak Presentasi Data Waktu Nyata Terowongan Angin Kecepatan Rendah Indonesia pada Perangkat Mobile Android - Ivransa Zuhdi Pane (Ultimatics : Jurnal Teknik Informatika, 2014)
Data presentation software is useful in presenting aerodynamics information for all stakeholders during a wind tunnel test execution. Development of such software in mobile devices, especially for displaying data in a real time manner, attracts the attention due to the promise in promoting the creation of more practical and more efficient test execution. Prototyping in Androidbased tablet and related test showed sufficient results to suggest further development of the prototype for the real application in the future. Index Terms—wind tunnel test, data presentation software, prototype, software engineering